Evaluation of Performance Indicator Development: A Study at The Ministry of Foreign Affairs of The Republic of Indonesia (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study evaluates the development of performance indicators using the performance blueprint analysis tool and determines the institutional factors that play a role in the development of performance indicators. Design/Methodology/Approach: Qualitative research with a case study approach was conducted at the Indonesian Ministry of Foreign Affairs (MoFA). Research findings: The Ministry of Foreign Affairs' performance indicator development has applied the principle of logical flow so that the programs and activities set have supported the strategic goals. In addition, most of the performance indicators include results and quality-oriented. However, weak documentation means that the logic flow is not well illustrated. This research captures the phenomena of isomorphism (coercive, mimetic, and normative), institutional logic, and institutional entrepreneurship in the performance measurement system (including the development of performance indicators) at the Ministry of Foreign Affairs. In addition, 15 institutional factors play a role in the development of performance indicators in the Ministry of Foreign Affairs, namely external parties, institutional idealism, initiation, efforts (related to accountability and performance indicator development), human resources, mindset, documentation, monitoring and evaluation, leadership commitment, logical framework principles, the role of stakeholders, business processes, reward and punishment, training, and information systems. Theoretical contribution/Originality: This research complements knowledge related to evaluating the development of performance indicators with performance blueprint analysis and institutional factors that play a role in the development of performance indicators, as well as knowledge about the phenomenon of institutional isomorphism, logic and entrepreneurship in government agencies. Practitioner/Policy implication: Ministries/agencies and regulatory agencies can use the performance blueprint analysis tool so that they can develop appropriate indicators and support policy making. Research limitation/Implication: The research focused only on the Ministry of Foreign Affairs, so the results do not reflect the development of performance indicators in other government agencies. In addition, the interviews did not take the point of view of external parties who have a relationship with the development of performance indicators of the Ministry of Foreign Affairs.